A review of the genus Enicospilus Stephens (Ichneumonidae: Ophioninae) from Vietnam, with descriptions of ten new species - Pham, Nhi Thi; Pham, Phu Van; Matsumoto, Rikio; Shimizu, So; Broad, Gavin R. (European Journal of Taxonomy, 2023)
Enicospilus Stephens, 1835 is the largest genus of subfamily Ophioninae (Ichneumonidae) with more than 700 extant species worldwide that are mostly nocturnal and parasitoids of larvae of Lepidoptera. In this paper, the Vietnamese species of Enicospilus are reviewed for the first time. Of the total 82 recorded species, 10 species are described as new: E. aequiscleritalis sp. nov., E. bulbipennis sp. nov., E. centraliscleritiger sp. nov., E. circuliscleritalis sp. nov., E. gialaiensis sp. nov., E. hiepi sp. nov., E. melanothoracicus sp. nov., E. nigristernalis sp. nov., E. trui sp. nov., and E. tuani sp. nov. Fifty-two species are recorded for the first time from the country: E. abdominalis (Szépligeti, 1906), E. acutus Shimizu, 2020, E. argus Gauld & Mitchell, 1981, E. atoponeus Cushman, 1947, E. bacillaris Wang, 1997, E. bakerielli Gauld & Mitchell, 1981, E. bifasciatus (Uchida, 1928), E. biharensis Townes, Townes & Gupta, 1961, E. concentralis Cushman, 1937, E. corculus (Tosquinet, 1903), E. dasychirae Cameron, 1905, E. eastopi Gauld & Mitchell, 1981, E. enicospilus Nikam, 1972, E. exaggeratus Chiu, 1954, E. fittoni Nikam, 1980, E. flavocephalus (Kirby, 1900), E. formosensis (Uchida, 1928), E. fusiformis Chiu, 1954, E. gasteralis Nikam, 1980, E. grandis (Cameron, 1905), E. hamatus Gauld & Mitchell, 1981, E. hedilis Gauld & Mitchell, 1981, E. iapetus Gauld & Mitchell, 1981, E. insinuator (Smith, 1860), E. ixion Gauld & Mitchell, 1981, E. javanus (Szépligeti, 1910), E. laqueatus (Enderlein, 1921), E. longitarsis Tang, 1990, E. mythrus Gauld & Mitchell, 1981, E. nathani Gauld & Mitchell, 1981, E. nigribasalis (Uchida, 1928), E. nigristigma Cushman, 1937, E. nigriventris Nikam, 1975, E. nigronotatus Cameron, 1903, E. nigropectus Cameron, 1905, E. pallidistigma Cushman, 1937, E. pantanae Tang, 1990, E. pinguivena (Enderlein, 1921), E. pseudoconspersae (Sonan, 1927), E. purifenestratus (Enderlein, 1921), E. rhetus Gauld & Mitchell, 1981, E. riukiuensis (Matsumura & Uchida, 1926), E. sauteri (Enderlein, 1921), E. selmatos Chiu, 1954, E. strigilatus Tang, 1990, E. teleus Gauld & Mitchell, 1981, E. transversus Chiu, 1954, E. tripartitus Chiu, 1954, E. urus Gauld & Mitchell, 1981, E. verticinus (Roman, 1913), E. yonezawanus (Uchida, 1928), and E. zebrus Gauld & Mitchell, 1981. A key to all Vietnamese species of Enicospilus is provided. A correction has been published: Pham N.T., Pham P.V., Matsumoto R., Shimizu S. & Broad G.R. 2023. A review of the genus Enicospilus Stephens (Ichneumonidae: Ophioninae) from Vietnam, with descriptions of ten new species – Corrigendum. European Journal of Taxonomy 879: 188–189. https://doi.org/10.5852/ejt.2023.879.2171